Synthesis and Characterizations ofN2(Aryl)-N4, N6-bis (6, 7-dichloro-1, 3-benzothiazol-2-yl)-1, 3, 5-triazine-2, 4, 6-triamines as Biological Potent Agents - B. B. Baldaniya (E-Journal of Chemistry, 2010)
Some novel N2-(Aryl)-N4, N6-bis (6, 7-dichloro-1, 3-benzothiazol-2-yl)-1, 3, 5-triazine-2, 4, 6-triamines (4a-u) have been synthesized and characterized by elemental analyses, IR, NMR, and mass spectra. The products have been tested for their antibacterial activity against gram (+)ve and gram (-)ve bacteria and also on different strains of fungi. Introduction of –OH, -OCH3, -NO2, -Cl and –Br groups to the heterocyclic frame work enhanced antibacterial and antifungal activities.